Effect modification of hypertension on the association of vitamin D deficiency with severity of coronary stenosis. (4th May 2018) - Li, Kuibao; Zhao, Wenshu; Wang, Lefeng; Yang, Xiyan; Yang, Xinchun
Abstract: Aims: There may exist an effect modification of hypertension on the relation of vitamin D deficiency with cardiovascular disease. The aim of this study was to investigate this interaction on coronary heart disease. Methods: We investigated 348 consecutive patients (mean age 62.4 ± 10.5 years; 56.3% male) who underwent coronary angiography because of chest discomfort at our heart center. Serum 25-OH vitamin D was also detected by ELISA method in these patients. Multivariable logistic regression models were used to estimate odd ratios (ORs) of CHD across vitamin D levels in hypertensives and normotensives, respectively. Results: We found the multivariable-adjusted ORs of CHD in the bottom(≤8.5 ng/ml) and middle tertiles (8.5–13 ng/ml) of 25-OH vitamin D were 2.86 (95% confidence interval [CI]: 1.38, 5.92) and 1.63 (0.83, 3.20), respectively, compared with those in top tertiles (>13ng/ml) among hypertensives (Ptrend =0.005). In contrast, the corresponding ORs of the above two groups were 0.88 (0.28, 2.74) and 1.23 (0.42, 4.00), respectively, in the normotensives (Ptrend  = 0.800; Peffect modification  = 0.020). The multivariable-adjusted OR of CHD in patients with severe hypovitaminosis D (<10 ng/ml) versus those with higher vitamin D (≧10 ng/ml) was also greater in hypertensives (2.76; 95% CI: 1.51, 5.04) than that in normotensives (0.92; 95% CI: 0.37, 2.33; Peffect modification =0.013). Similar results were observed when Gensini Score was treated as a dependent variable. Conclusion: Our finding suggests the presence of hypertension may modify the association of vitamin D deficiency with severity of coronary stenosis.